Implementation of E-Book Creation Using a Culture and Civic Literacy Approach in Elementary Schools - Hermawan, Jody Setya; Rizqi, Yoga Fernando; Ningrum, Sevia Palupi Dwi; Ayudista, Shakina Aura (ICSIGER- International Conference on Science and Emerging Technology, 2025)
The e-book development strategy is a significant initiative designed to improve students’ cultural literacy by incorporating local wisdom values into the educational framework. This methodology emphasises the importance of local culture, traditions, and life experiences as essential components for effective pedagogical practices. The initial stage of this process involves identifying relevant cultural elements, such as folklore, customs, regional dialects, and traditional values that are appropriate for the student demographic. These cultural components are carefully integrated into the e-book content, in line with the competencies outlined in the national curriculum. To enhance student engagement, the e-book is developed with interactive features that combine visual, auditory, and video media, thereby enriching the cultural understanding experience. The use of contextual and communicative language fosters a deeper connection between students and the instructional material presented. Additionally, the e-book includes reflective and creative activities, such as cultural projects, documentation of family traditions, or the creation of inspiring folk tales. This pedagogical approach makes the learning experience meaningful, enjoyable, and relevant, while respecting and instilling pride in cultural heritage. As a result, e-books not only enhance academic understanding but also play an important role in shaping students’ character and cultural identity in the digital age.